PENGEMBANGAN MEDIA FLIP FLAP BOOK INTERAKTIF BERBASIS GAME BASED LEARNING PADA MATERI KALIMAT EFEKTIF SISWA KELAS IV SDN 1 TRENCENG KABUPATEN TULUNGAGUNG - Maharani, Tantias Widya; Hayuhantika, Diesty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is based on the fact that fourth-grade students lack learning media that help them understand the material on effective sentences. This is because the media used by teachers are monotonous and fail to engage students. The purpose of this study is to describe the development, validity testing, and practicality testing of an interactive Flip Flap Book learning medium based on Game-Based Learning that focuses on the material of effective sentences for fourth-grade elementary school students. This study employed a research and development approach using the ADDIE model. The research subjects involved in the pilot test included experts in the fields of media, content, and language; a classroom teacher; and 18 fourth-grade students from SDN 1 Trenceng as users. Data collection techniques utilized several instruments, including questionnaires, observations, and documentation. The media validation result reached 96.1% with a “Highly Valid” rating, the content validation reached 95.1% with a “Highly Appropriate” rating, and the language validation reached 94.8% with a “Highly Appropriate” rating. Meanwhile, the practicality test via the teacher response questionnaire yielded a percentage of 91.6% with a rating of “Very Practical,” and the response questionnaire from the 18 fourth-grade students at SDN 1 Trenceng resulted in an average percentage of 87.5% with a rating of “Very Practical.” The final results of the study demonstrate that the interactive Flip Flap Book medium, based on Game-Based Learning and designed for teaching effective sentences, is highly valid and very practical for use in the learning process at the elementary school level.